ANTIFUNGAL ACTIVITY POTENTIAL AND VOLATILE COMPOUND PROFILE OF Bacillus sp. HSFI-6 Extract - Maya Dian Rakhmawatie; Mazidatu Khoirinnisa’ Adiyanti; Nur Fadhila Sari; Fadhil Widya Dharma Putra; Kanti Ratnaningrum; Ika Dyah Kurniati; Devita Diatri (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Antifungal resistance has implications for the development of bioactive compounds. Bacillus sp. has been widely studied for the discovery of antifungal volatile compounds. This study aims to explore the antifungal activity of Bacillus sp. HSFI-6 isolated from sea cucumber (Holothuria scabra Fermented Intestine-HSFI) against Malassezia furfur, Candida albicans, and Aspergillus fumigatus. Bacillus sp. HSFI-6 was identified molecularly by 16S rRNA sequencing. Ethyl acetate extract of Bacillus sp. HSFI-6 was produced using media containing starch, yeast, peptone, and its metabolites were profiled using Gas Chromatography-Mass Spectroscopy (GC-MS). A disc diffusion antifungal assay was performed. Bacillus sp. HSFI-6 has 93.47% similarities with Bacillus albus strain MCCC 102146 and moderately inhibit C. albicans (7.00 ± 1.15 mm), A. fumigatus (9.25 ± 0.96 mm). The GC-MS metabolomics analysis showed two antifungal volatile compounds, namely cycloheptasiloxane, tetradecamethyl- and cyclononasiloxane, octadecamethyl-. These results conclude that Bacillus sp. HSFI-6 is suitable for the development of antifungal drugs.